Intellectual property business protection during a company survival stage : an inside-out approach - Vergara Sandoval, Matias (Intellectual Property Research Unit, 2016)
Lawyers and businessmen work closely together every day. Despite the increasing value of patents and trademarks for companies, it is important to keep in mind that Intellectual Property law and contractual law provide for much more types of protection than statutory rights (patents, trademarks, copyright). Business and company developments are no longer linear. Flexibility plays a key role in the journey a company has to travel to reach success, especially in the case of entrepreneurs and sole proprietorship companies. New businesses going through the "death valley"1 will need to be as flexible as possible to succeed. It is only fair for their attorneys to meet such flexibility standard. For these purposes, understanding different industries, stages of business developments, and Intellectual Property contractual and statutory rights becomes an essential matter to properly asses which kind of protection should and can be used for a particular scenario, on a specific time and on a limited budget. In general terms, Intellectual Property literature presents different types of Intellectual Property management schemes making use of patents, trademarks, design models, copyright, etc. individually considered and mainly referring to statutory or agency granted rights. These mainly and usually refer to case law and /or jurisprudence (as applicable) and international conventions. However, despite the ever increasing number of articles addressing each of these rights, little reference is made to their strategic use within the context of a specific company's business development stage or business needs they are aiming to protect. When reflecting on success cases, not many details are published regarding the "partnership agreements", "employment contracts", "services agreement" entered into by a company, or the Intellectual Property policies implemented by it while developing its business. On the other hand, when addressing the Intellectual Property portfolio, authors seem to refer to patents, trademarks and copyright as the big (or even core) concerns. Consequently, what matters should an entrepreneur identify and address from an Intellectual Property standpoint when starting a business? The most common answer has been: I am just starting and not anywhere near to a patent, so that is not for me. Each Intellectual Property statutory right functions independently, notwithstanding the possibility of using a combination of them. However, these rights can be used for more than one purpose. This dissertation describes the legally granted privileges (focused on patents, trademarks, copyright) and the role these play, just as one of the tools entrepreneurs have to protect their Intellectual Property business. It describes and explains other available contracting tools as part of a comprehensive Intellectual Property protection and business development strategy.